Measurement of the tt̄ cross section using high-multiplicity jet events - Abazov, V. M. (2010)
We present a measurement of the tt̄ cross section using high-multiplicity jet events produced in pp̄ collisions at √s=1.96TeV. These data were recorded at the Fermilab Tevatron Collider with the D0 detector. Events with at least six jets, two of them identified as b jets, were selected from a 1fb-1 data set. The measured cross section, assuming a top quark mass of 175GeV/c2, is 6.9±2.0pb, in agreement with theoretical expectations. © 2010 The American Physical Society.